Plane waves in anisotropic elastic–plastic material with voids. (February 2022) - Kumar, Suraj; Tomar, Sushil Kumar
Dispersion equation is derived for the propagation of one-dimensional plane waves in a general linear anisotropic isothermal elastic–plastic material with voids. The plasticity of the considered material is defined through the dislocation of a single slip plane and direction. The derived dispersion equation is then reduced for the relevant wave propagation in particular media, namely, monoclinic, orthotropic, transversely isotropic, and isotropic elastic–plastic material with voids. In general, it is found that there exist four basic waves traveling with distinct speeds in these specific anisotropic elastic–plastic materials with voids. A new wave is found to appear because of the presence of plasticity in the material. Out of the four basic waves traveling in an orthotropic/transversely isotropic material with voids, a wave travels independent of plasticity and void parameters, whereas the remaining three waves depend on plasticity as well as on the presence of voids. The one which is traveling independent of plasticity and voids is nondispersive and nonattenuating, whereas the other waves are dispersive in nature. The speeds of all the existing waves are computed numerically for a specific model, displayed graphically, and discussed.